Pendidikan Islam Dalam Perspektif Filsafat Idealisme - Yanuarti, Eka (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2016)
Idealism is a flow of philosophy that emphasizes the importance of excellence thoughts (mind), soul or spirit instead of the things that are related to immaterial or material. The nature of a human is the soul or the spirit, called